A comparison of fecal sampling and direct feeding observations for quantifying the diet of a frugivorous primate. Issue 4 (26th November 2019) - Matthews, Jaya K; Ridley, Amanda; Kaplin, Beth A; Grueter, Cyril C
Abstract: Both observational and indirect evidence are widely used to determine the diets of wild animals. Direct observations are often assumed to provide the most comprehensive reflection of diet, but many wild animals are logistically challenging to observe. Despite the regular use of observational and indirect methods for inferring diet in wild animals, they have rarely been compared in detail for the same study population. Over 12 months this study assessed the congruence of methods in estimating the diet of a montane community of eastern chimpanzees Pan troglodytes schweinfurthii in Nyungwe National Park, Rwanda using observational scan samples and macroscopic fecal inspection. The assessment of the number of food species consumed each month was comparable between methods, but the estimation of the composition of items in the diet differed significantly. Most notably, the fecal samples significantly underestimated the consumption of flowers, and certain fruit species, which based on direct behavioral observations were seasonally consumed at very high rates. Conversely, direct observations underestimated the consumption of leaves and pith in comparison to results present in the fecal samples. These results suggest that combining methods where possible is most useful for accurate monitoring of dietary trends, particularly for species that experience significant seasonal shifts in their diet.